2019
DOI: 10.1111/jpy.12826
|View full text |Cite
|
Sign up to set email alerts
|

Temperature × light interaction and tolerance of high water temperature in the planktonic freshwater flagellates Cryptomonas (Cryptophyceae) and Dinobryon (Chrysophyceae)

Abstract: Using microcosm experiments, we investigated the interactive effects of temperature and light on specific growth rates of three species each of the phytoplanktonic genera Cryptomonas and Dinobryon . Several species of these genera play important roles in the food web of lakes and seem to be sensitive to high water temperature. We measured growth rates at three to four photon flux densities ranging from 10 to 240 μmol photon · m −2 · s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Interestingly, a significant interaction between the two factors temperature and irradiance was also observed for the maximum growth rate. Generally, the interaction between these two factors results in lmax increasing with temperature under light saturation (Ojala 1993, Edwards et al 2016, Wirth et al 2019. However, our results showed that lmax was strongly affected at temperatures higher than the optimal one when irradiance was high.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Interestingly, a significant interaction between the two factors temperature and irradiance was also observed for the maximum growth rate. Generally, the interaction between these two factors results in lmax increasing with temperature under light saturation (Ojala 1993, Edwards et al 2016, Wirth et al 2019. However, our results showed that lmax was strongly affected at temperatures higher than the optimal one when irradiance was high.…”
Section: Discussionmentioning
confidence: 54%
“…, Wirth et al. ). However, our results showed that μmax was strongly affected at temperatures higher than the optimal one when irradiance was high.…”
Section: Discussionmentioning
confidence: 99%
“…This "thermal safety margin” should allow many species to cope with global warming (Krenek et al 2012). However, in the course of climate change, the UTTL of temperature‐sensitive protist species may constrain their distribution and lead to a shift in the species composition (Montagnes et al 2008; Wirth et al 2019).…”
Section: Figurementioning
confidence: 99%
“…Readers unfamiliar with the intricacies of the FlowCam are unlikely to understand from the methods presented that most papers do not make use of the widely advertised auto‐classification capabilities of the device. The statement that classifications were conducted “using VisualSpreadsheet software,” employed by many papers (Bergkemper and Weisse 2017; Fileman et al 2017; Wirth et al 2019), is insufficient given that this software can be used solely for processing samples through the FlowCam, for auto‐classifications of images produced by the FlowCam or simply as an image‐viewing interface for manual sorting of images. Furthermore, some papers have provided detailed explanation in their methods section of the creation of image libraries for the apparent purpose of auto‐classification, only to reveal later in the discussion section that the image library was not used or tested in the study (Park et al 2019 a ).…”
Section: Discussionmentioning
confidence: 99%